USAHA MENINGKATKAN KETERAMPILAN BINA DIRI ANAK AUTIS MELALUI METODE ANALISIS PERILAKU TERAPAN PADA SLB (Sekolah Luar Biasa) - Wayan Loh Lasmini; Agus Wibowo; Satrio Budi Wibowo (Counseling Milenial (CM), 2024)
This study aims to determine the implementation of the ABA method applied in SLB Insan Madanı Metro. This research is a qualitative design with a descriptive type of research. Data collection techniques consist of interviews and observations. The results of the study can be concluded, (1) At the planning stage of the ABA method in developing the self-development ability of Autism Spectrum Disorder children, namely conducting a need assessment then establishing a diagnosis and providing a special program, namely ABA, (2) At the stage of implementing the Applied Behavior Analysis method in developing children's self-development abilities Autism Spectrum Disorser (ASD) ABA therapy using techniques, namely DTT from instructions, prompt feedback and reinforcement, (3) The results of the implementation of the ABA method, namely the ABA method, are effective in helping ASD children develop self-development skills, this is evidenced by O. K. H and D children's independence in fostering self is good Evaluation carried out by psychologists is carried out once every three months based on notes from the teacher then synchronized with a special program, namely ABA.Keywords: self development